2021
DOI: 10.3390/antibiotics10091124
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Antibiotic Usage on Small-Scale Dairy Farms in the Indian States of Assam and Haryana Using a Mixed-Methods Approach—Outcomes and Challenges

Abstract: The use and misuse of antibiotics in both humans and animals contributes to the global emergence of antimicrobial resistant (AMR) bacteria, a threat to public health and infection control. Currently, India is the world’s leading milk producer but antibiotic usage within the dairy sector is poorly regulated. Little data exists reflecting how antibiotics are used on dairy farms, especially on small-scale dairy farms in India. To address this lack of data, a study was carried out on 491 small-scale dairy farms in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 27 publications
2
31
0
Order By: Relevance
“…Seven reports were excluded: one was a literature review of drivers of AMR [ 33 ]; one included domestic animals instead of farm animals [ 34 ]; three reports were indirect methods of quantification of ABU/AMR [ 20 , 35 , 36 ]; and two articles were conference reports [ 37 , 38 ]. Seventeen studies, described in 18 publications [ [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] ], were included in the scoping review.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Seven reports were excluded: one was a literature review of drivers of AMR [ 33 ]; one included domestic animals instead of farm animals [ 34 ]; three reports were indirect methods of quantification of ABU/AMR [ 20 , 35 , 36 ]; and two articles were conference reports [ 37 , 38 ]. Seventeen studies, described in 18 publications [ [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] ], were included in the scoping review.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Contaminated dairy products with AMG antibiotics are of health concern [86][87][88][89], which attracted public attention from different parts of the world [90,91]. We apply our method to detect streptomycin spiked milk samples to assess the practical applicability of His@AuNPs.…”
Section: Applicability Of the Detection Systemmentioning
confidence: 99%
“…India is a country with a large livestock population ( 12 , 13 ). Antibiotics are extensively misused in the dairy sector and residues remain largely untested in milk, which is an essential part of Indian diets ( 8 , 14 , 15 ). Antibiotics are commonly used as growth promoters in livestock, such as poultry, however the real extent of this practice is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…There is a lack of evidence regarding the extent to which farmers are aware about the effects of antibiotic use, its residues, and resistance. Nevertheless, a few studies have revealed a poor level of knowledge among the dairy farmers about both antimicrobial residues and resistance ( 14 , 18 , 19 ). It has been observed that some farmers treat their animals with antibiotics regardless of whether the disease is caused by bacteria or not, and often they are not even aware that the drug is an antibiotic ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation